Analysis of a Prefabricated Structure Considering Lateral Load Using ETABS A Review - Kukreja, Nitin; Nirmal, Mr. Pradeep Kumar (International Journal of Scientific Research in Civil Engineering, 2023)
Precast concrete is an alternative to cast-in-situ concrete. While cast-in-situ concrete is cast in its actual location, precast concrete is cast at another location, either at the building site or in a factory, and is then lifted to its final resting place and fixed securely. This means that unlike cast-in-situ construction, which is monolithic or continuous, precast concrete buildings are made of separate pieces that are bolted or connected together. In India, greatest constructional exercises are finished utilizing the old conventional cast in situ strategies since seemingly forever. As the nation is creating in a high speed, the necessity for lodging is heightening and in this way the development ventures are additionally blossoming quickly henceforth requesting quicker and better development techniques. This expanded interest can be coordinated by utilizing one of the cutting-edge innovations, pre-projected substantial strategy. Investigation of writing shows various priority of precast constructional strategy over different techniques for development.
Keywords: Conventional Cast in Situ Method; Etabs; Pre-Cast Concrete Method; Seismic Analysis